Parasitoses intestinales dans la zone du complexe hydroagricole du Sourou au Burkina Faso - D. Dianou; Jean-Noël Poda; L.G. Savadogo; H. Sorgho; S.P. Wango; B. Sondo (VertigO, 2004)
In the Sourou valley, parasitological surveys on the prevalence of intestinal parasite infections were carried out between 2000 and 2002 in the traditional villages of Wèrè, Toma-île, Yayo, Touroukoro, Di located on the lake and on the waterlogged zones, and Oué, Sono located at about 10 kilometers from the lake. The parasitological surveys were also carried out in the constructed sites of Débé, Guiédougou and Niassan. In order to determine the prevalence and the intensity of intestinal parasite infections in the studied sites, stools of 1142 children of 0 to 16 years old were examined.Globally the results showed overall prevalence of 46.5% for intestinal parasite infections with 20.9% for Schistosoma mansoni, 10.6% for Entamoeba hystolytica (amibe kystes), 10.2% for Hymenolepis nana (tape worm), 1.6% for Necator americanus (hookworm), 1.1% for Giardia intestinalis (kystes) and Strongyloïdes stercolaris. Other intestinal parasites were also present however, at low prevalence level (Ascaris lumbricoïdes, Trichuris trichiura). The results especially pointed out a high difference in prevalence rate related to the studied site location. The villages located in the waterlogged zones and especially on the lack showed the highest prevalence rates for overall intestinal parasite infections (77.1%, 60.2%, 50.0%, 48.4%, and 45.7%) and for Schistosoma mansoni (53.7%, 54.1%, 43.3%, 22.1%, and 22.5%) in Toma-île, Wèrè, Touroukoro, Yayo, and Di, respectively, compared to the ones located at 10 kilometers from the lake (0% in Oué and Sono for Schistosoma mansoni).Findings suggest that implementation of a program to reduce and control the intestinal parasite infections is needed in the hydroagricultural zone of Sourou.